Kutchin family outside home, Forty Mile City, Yukon, ca. 1899 - Hegg, Eric A., 1867-1948
Family group, possible Kutchin Indians, outside house, ca. 1898-1900. Beside them is dogsled, tent next to building, possibly sod-house. Caption on image: An Indian family at home, Forty Mile City, Dawson Copied by Webster & Stevens 265.A